Tithinirṇaya: A Calendrical Text of the Mādhva Tradition for Religious Observations - Yelluru, Nagakiran; Sreeram, G.; Pai, Venketeswara R.; Kolachana, Aditya (History of Science in South Asia, 2025)
Tithinirṇaya is a celebrated astronomical text of the Mādhva tradition, intended primarily to assist in computing the appropriate days for observing a religious fast. For this purpose, it prescribes a procedure to obtain the tithi at sunrise for an observer located at latitude (φ) near 12.780. This work supplies a translation of the text along with mathematical and geometric rationales for the astronomical algorithms presented therein, which are either inadequate or missing in prior publications. The work also investigates the disputed authorship of the text and briefly remarks upon its religious applications.